2022
DOI: 10.3389/fpubh.2022.1006391
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological characteristics and survival analysis on patients with occupational pneumoconiosis in Zhejiang Province from 1987 to 2019

Abstract: ObjectiveTo evaluate risk factors affecting survival in patients diagnosed with pneumoconiosis and propose strategies to improve the quality of life in these patients.MethodsThe basic patient information was obtained from the pneumoconiosis report card. Disease types, regions, and industry distribution of pneumoconiosis were analyzed. The Kaplan-Meier survival curves and the Cox proportional risk regression model was used for survival analysis.ResultsA total of 13,812 patients were diagnosed with pneumoconiosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
0
3
1
Order By: Relevance
“…In terms of different types of pneumoconiosis, this study found no significant differences in the survival curves among the three categories, which is consistent with a study conducted in Jiangsu Province [ 12 ]. However, we did not observe statistically significant differences in survival among different stages of pneumoconiosis in this study, which is inconsistent with a previous study conducted in Zhejiang Province [ 18 ]. This discrepancy in findings may be attributable to the smaller number of stage III patients in our study and the relatively similar survival status between stage II and stage I patients.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In terms of different types of pneumoconiosis, this study found no significant differences in the survival curves among the three categories, which is consistent with a study conducted in Jiangsu Province [ 12 ]. However, we did not observe statistically significant differences in survival among different stages of pneumoconiosis in this study, which is inconsistent with a previous study conducted in Zhejiang Province [ 18 ]. This discrepancy in findings may be attributable to the smaller number of stage III patients in our study and the relatively similar survival status between stage II and stage I patients.…”
Section: Discussioncontrasting
confidence: 99%
“…Pneumoconiosis poses a serious threat to the health of workers and places a significant burden on society, affecting millions of workers worldwide who engage in hazardous occupations [ 18 ]. It is one of the common occupational diseases in China.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As workers age, lung ventilation function decreases significantly, and dust or debris from processed materials can be inhaled by workers. Long term work can lead to the occurrence of occupational pneumoconiosis [16][17] . The length of service exposed to dust is an independent risk factor for the occurrence of occupational pneumoconiosis.…”
Section: Discussionmentioning
confidence: 99%